PREPARATION OF FACILITIES OF SMALL MECHANIZATION FOR STORAGE - Ляшенко, С. В. (Scientific Progress & Innovations, 2015)
The analysis of technological operations of preparation of WEIMA 900M to storage is considered. Improved technological process of preparation of motocultivator to storage, due to development of recommendations necessary to implementation. Control the system of storage of small mechanization’s facilities, which is based on collection and use of database about damages and breakages which arise in the period of storage of technique, is offered. Due to the developed system, possibility to control the technical state during the period of exploitation appeared.